Shalawat sebagai Spiritual Coping dalam Intervensi Psikoterapi dan Konseling Islam untuk Mengatasi Quarter-Life Crisis - Soffy Balgies; Lina Fastina; Agus Santoso (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the implementation of shalawat as a spiritual therapy in addressing Quarter Life Crisis among fresh graduate students. Quarter Life Crisis is defined as a phase of emotional and psychological crisis commonly experienced by individuals aged approximately 18–30 years, during which a person feels confused, anxious, and uncertain about the direction of their life. This research employed a qualitative approach through in-depth interviews, non-participant observation, and documentation. The research subjects were selected using purposive sampling based on their life experiences and their status as fresh graduate students. This study integrates Shalawat as a devotional practice and a form of spiritual therapy rooted in religiosity, enabling its application in daily life, particularly in dealing with Quarter Life Crisis issues. The integration of these two theoretical perspectives offers a spiritual therapeutic approach in which spiritual and psychological aspects mutually reinforce one another. The findings indicate that students' inner peace and self-confidence were strengthened through the combination of Shalawat practices and spiritual therapy, including self-control, optimism, and religious practices such as dzikr and self-reflection. Social support from the university environment, peers, and religious communities further enhanced individuals' resilience in facing the future. This study contributes theoretically to the fields of Sufism and Psychotherapy while also offering an interactive approach to support fresh graduate students in avoiding the phenomenon of Quarter Life Crisis